If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 12 + -5x + -14 = 17 Reorder the terms: 12 + -14 + x + -5x = 17 Combine like terms: 12 + -14 = -2 -2 + x + -5x = 17 Combine like terms: x + -5x = -4x -2 + -4x = 17 Solving -2 + -4x = 17 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + -4x = 17 + 2 Combine like terms: -2 + 2 = 0 0 + -4x = 17 + 2 -4x = 17 + 2 Combine like terms: 17 + 2 = 19 -4x = 19 Divide each side by '-4'. x = -4.75 Simplifying x = -4.75
| 1(3)x+11/2 | | 3/5x3/10 | | 3/5*3/10 | | 6-29=37 | | x+12+5x-14=17 | | 36+6c=60 | | 2/3(x-5)+1/2x+3 | | 4s+13=29 | | 8-4i/14i | | -6=x/12 | | -3x+5=-19 | | 1-5i/5+i | | 2x-1=97 | | (3p-8)/12=p/5 | | 3x+4=2x+2(x-7) | | (4x+1)(x-5)=0 | | (3p-8)/12=p/8 | | x^2(2x+3)=0 | | 0.5m+3=5 | | x(5x+3)=0 | | 3p-8/12=p/5 | | 5(3x+5)-12x=24 | | 14b^2-23b-15=0 | | 6x^2+7x=10 | | -4x+12.5=0.25x+4 | | 6x^2+x=10 | | 6x^2-29x-35=0 | | 4x-7=32x+14 | | 2x(x+3)(x-4)=0 | | y/9=6 | | 9x^2(x+4)=0 | | Y=3lnx |